THE OPPORTUNITIES OF CAMBRIDGE ANALYTICA DEVELOPED TECHNOLOGY IN EUROPE AND LATVIA - Kudiņa, Ilze; Mežinska, Liene; Smirnova, Jeļena; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
The aim of the paper is to research and analyse Cambridge Analytica developed technology opportunities in Europe and Latvia. To reach this goal authors gathered and analysed literature sources, and statistical data, and drew conclusions. Cambridge Analytica technologies provide both opportunity for development as well as poses a threat to Europe and Latvia. Based on OCEAN personality model, Big data and microtargeting opportunities, Cambridge Analytica developed a quantitative data processing tool that analyses given data and provides personality profile. Statistical data about Internet usage in Europe in 2015 and 2016 shows that the amount of internet users is constantly growing. The same applies to Latvia, furthermore the amount of worldwide Internet site usage in Latvia is growing as well, allowing for more data gathering and less privacy protecting regulations restrictions. Cambridge Analytica developed technologies enable microtargeting usage in Latvia to provide more efficient and cost-effective marketing in electronic environment to the economically active population of Latvia.